2019
DOI: 10.1055/a-0891-7021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mouthguards on Physiological Responses in Rugby

Abstract: Mouthguards (MGs) are highly recommended in rugby. Airway obstruction and a resulting decrease in power output are potential disadvantages of their usage. The aim of the study was to assess possible limitations of “vented” (MGV) and custom-made mouthguards (MGC) on rugby players’ performance. The MG effects were investigated in 13 male first-league rugby players ranging from 18–34 years old. First a lung function test was completed. Then a double incremental treadmill test was performed to measure maximum aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 30 publications
2
32
1
Order By: Relevance
“…Overall, it can be assumed that the nMG reduces the sympathetic tonus in the present study [19]. The ergogenic effect described so far with the MG [12,24,25,37] thus appear to be dependent on the load requirement.…”
Section: Reduced Peripheral Breathing Reflexessupporting
confidence: 50%
See 4 more Smart Citations
“…Overall, it can be assumed that the nMG reduces the sympathetic tonus in the present study [19]. The ergogenic effect described so far with the MG [12,24,25,37] thus appear to be dependent on the load requirement.…”
Section: Reduced Peripheral Breathing Reflexessupporting
confidence: 50%
“…Studies found that this type of MG reduced ventilation (V E ) without negatively affecting performance or oxygen uptake. It was also found that when using these self-adapted MGs with breathing channels, blood lactate was often lower compared to that with the use of a traditional self-adapted MG or no MG [9][10][11][12]. These results suggest improved alveolar V E , which potentially increases respiratory efficiency.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations